Effectiveness of Integrating Educational Games in Physical Fitness Training to Improve Students Cardiorespiratory Capacity - Indra Maulana; Baiq Satrianingsih; Susi Yundarwati; Dadang Warta Candra Wira Kesuma (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Background: Cardiorespiratory capacity (CRF) is crucial for physical and cognitive health in children and adolescents. However, declines in CRF due to sedentary lifestyles highlight the need for effective interventions in school-based physical education (PE) programs. Traditional PE methods often fail to engage students sufficiently. Objective: This systematic literature review (SLR) evaluates the effectiveness of integrating educational games into physical fitness training, comparing it with traditional high-intensity interval training (HIIT) for improving CRF in students. Methods: A systematic search across Scopus, Web of Science, and Google Scholar identified experimental and quasi-experimental studies from the last 10 years. Studies included were those that integrated educational games into fitness programs and measured CRF outcomes. Results: HIIT consistently improved CRF, particularly VO₂ max and aerobic performance. Game-based interventions showed smaller but significant improvements, primarily through enhanced engagement and motivation. Combining game elements with HIIT enhanced both physiological and behavioral outcomes. Conclusion: HIIT and game-based interventions offer complementary benefits for improving CRF. HIIT provides significant physiological gains, while educational games foster long-term participation. A combined approach could optimize both fitness and engagement in PE programs. Further research is needed to refine intervention parameters and assess long-term outcomes.